Cirrhosis associated with multiple transfusions in thalassaemia. Issue 1 (January 1984) - Jean, G; Terzoli, S; Mauri, R; Borghetti, L; Di Palma, A; Piga, A; Magliano, M; Melevendi, M; Cattaneo, M
Abstract : The study of surgical liver biopsy specimens obtained during splenectomy in 86 children with thalassaemia indicated that such patients may develop liver disease that evolves into cirrhosis. Histological characteristics suggest that it is post-necrotic cirrhosis. Onset of cirrhosis in some patients may occur as early as 7-8 years old, and at age about 15-16 years most children with thalassaemia show features of cirrhosis. In addition to fibrosis, hepatitis, or even aggressive hepatitis may develop as has also been observed in patients without thalassaemia who have undergone multiple transfusions. This study presents the current probable evolution of liver disease in patients with thalassaemia and may thus serve as a reference from which to evaluate any future progress in the treatment and care of patients with Cooley's disease.